Network Effects and the Dynamics of Migration and Inequality: Theory and Evidence from Mexico - David Mckenzie; Hillel Rapoport (Bar-Ilan University, Department of Economics, 2004)
International migration is costly and initially only the middle class of the wealth distribution may have both the means and incentives to migrate, increasing inequality in the sending community. However, the migration networks formed lower the costs for future migrants, which can in turn lower inequality. This paper shows both theoretically and empirically that wealth has a nonlinear effect on migration, and then examines the empirical evidence for an inverse U-shaped relationship between emigration and inequality in rural sending communities in Mexico. After instrumenting, we find that the overall impact of migration is to reduce inequality across communities with relatively high levels of past migration. We also find some suggestive evidence for an inverse U-shaped relationship among communities with a wider range of migration experiences.
Keywords: O15; J61; D31; 330; Migration; remittances; inequality; network effects